Postharvest Disease Development Pre and/or Postharvest Practices - Fallik, Elazar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Postharvest losses of fresh produce have always been an obstacle in agriculture. About one third of global fresh fruits and vegetables are lost because their quality has dropped below an acceptance limit. The postharvest quality and shelf life of fresh produce are also determined before harvest. However, postharvest quality is also affected by many practices during and after harvest such as temperature management, controlled and modified atmosphere, coatings, physical treatments, biocontrol, and more. This Special Issue on "Postharvest Disease Development: Pre and/or Postharvest Practices" gathers papers that deal with preharvest and postharvest factors that affect and maintain fresh produce quality after harvest.